STANDART PELAYANAN MINIMAL (SPM) DAN SISTEM LASING PADA KAPAL RO-RO UNTUK KESELAMATAN TRANSPORTASI PENYEBRANGAN LAUT (Studi Kasus KMP. LEGUNDI) - Ariany, Zulfaidah; Hendra, A; Febriary, Samual (Vocational School Diponegoro University, 2018)
Zulfaidah Ariany, A Hendra, Samual Febriary, in this paper explain that LEGUNDI is a Passanger Ship which has a Surabaya - Lombok shipping route capable of transporting passengers and vehicles in relatively large numbers. Research Minimum Service Standards (SPM) and Lasing System on Ro-Ro Ship for Marine Transportation Safety is aimed to know about Minimum Service Standards (SPM) and how to handle the Lasing system on Ro-Ro KMP LEGUNDY. The reference used is Minister of Transportation Regulation no 30 of 2016 regarding minimum service standard. The analysis used is simulation of shear load calculation on vehicle in Car Deck so get output layout of vehicle parking layout. The result of simulation of the calculation got the total load when the car shifted 35,5 KN then it can be suggested using breaking strength: 60 kN (6 ton) and Weight 0.35 kg based on Break Load Capacity Table for Chain Lasingbe typed in one paragraph and one-column format.